TRACER STUDY MASTER ADMINISTRATION OF EDUCATION OF UHAMKA AS THE INTENTION OF THE EDUCATIONAL TRANSFORMATION PROGRESS - Ihsana El KHULUQO; Rismita RISMITA (Journal of Education and Leadership in Education, 2020)
The research objective of this tracer study master's degree in educational administration is as an effort to see the progress of university transformation (UHAMKA) regarding the relevance of knowledge and skills acquired while criticizing higher education which is beneficial to society in general and its recognition, and as an evaluation material for decision making. The research methodology is a mix method that combines qualitative and quantitative forms. The model used is Sequential Explanatory, which means the collection and analysis of quantitative data is followed by the collection and analysis of qualitative data by calculating the frequency distribution of each indicator. Quantitative data collection was carried out by survey techniques, using qualitative descriptive and distributing questionnaires to 24 respondents. The findings show that the provision of competency for graduates can be relied upon by emphasizing the effectiveness of higher education in providing quality education and education services, which is shown by the recognition of the society for graduates who are able to change the order of life with noble character that is desired by society in general.